FROM RUNNERS TO READERS: HOW STUDENTS PERCIEVE THE USE OF RUNNING DICTATION IN READING COMPREHENSION - Mega Triana; Pratnyawati Nuridi Suwarso; Dian Novita Dewi (IAIN Syekh Nurjati Cirebon, 2024)
Most students struggle with reading comprehension, often not meeting the curriculum standards. For this reason, a strategic approach is needed to enhance students' comprehension in reading, which makes them more interested in continuing to learn, one of which is the application of running dictation techniques. Therefore, this research aims to determine students' perceptions of the running dictation technique implemented in the reading comprehension classroom. This research used a quantitative method with a survey approach. A purposive sampling technique was used to select 36 students of tenth graders from one public school in Malang Regency. The questionnaire covers five dimensions Students' motivation, student perception of reading comprehension, students' attitude toward the implementation of the running dictation technique, students' subjective Norms toward implementation of the running Dictation technique, and students' perceived behavioral control towards the implementation of running dictation. The result revealed that the mean scores ranged from 2.95 to 3.07, indicating a generally positive perception in all dimensions. The highest average score of 3.07 was for students’ attitude toward the technique, indicating they find the technique effective and beneficial. The lowest average score of 2.95 was for students’ perception of their reading comprehension. This lower perception suggests that students still struggle with understanding English texts. This should be a concern for teachers to further train students in comprehensive reading with critical thinking so that students can find the implied meaning in each reading.